A case report: black oesophagus as a possible complication of transcatheter aortic valve implantation. Issue 2 (3rd June 2019) - Gonçalves, Inês S; Bordalo e Sá, Armando L; Fatela, Narcisa; Canas da Silva, Pedro
Abstract: Background: The increasing number of transcatheter aortic valve implantation (TAVI) in the last few years has unveiled a unique set of events and complications that need prompt recognition and management in order to improve patient outcomes, often involving a multidisciplinary team. Case summary: We present a case of a 86-year-old woman with symptomatic severe aortic stenosis that underwent a TAVI and, in the post-procedure period, presented with acute abundant haematemesis, haemodynamic instability, and haemoglobin drop. The diagnosis of acute necrotizing oesophagitis (ANE) was made by upper gastrointestinal endoscopy. Discussion: Acute necrotizing oesophagitis is a rare entity caused usually by an ischaemic insult in the presence of predisposing factors; it has a high rate of complications and mortality. To the best of our knowledge, this is the first clinical case report to describe the occurrence of ANE as a possible complication of TAVI and is also an example of the importance of the multidisciplinary approach of these complex patients, which extends even beyond the concept of Heart Team.